Patient safety attitudes and their predictors among emergency healthcare providers in a military medical city in the Kingdom of Saudi Arabia: a cross-sectional study - Alotaibi, Adel Saeed S.; Alshehri, Salem Ali S.; Alanazi, Naif H.; Alshehry, Abdualrahman S.; Alharbi, Homood A.; Alanazi, Abdulmajeed Wadid A.; Alkhalaf, Ali Ahmed M.; Tumala, Gerlynn C.; Alotaibi, Abdulaziz Moadi B.; Alfaifi, Mohammed Ahmed; Tumala, Regie B. (Frontiers in Medicine, 2025)
BackgroundThe increase in the number of patient safety incidents poses a challenge for hospital management. Various studies have been conducted on the safety of patients in healthcare settings, but gaps exist concerning the attitude of healthcare providers (HCPs) toward the safety of patients, including those in the emergency department (ED) in Saudi Arabian hospitals.AimThis study aimed to determine the attitude of HCPs toward patient safety in the ED at Prince Sultan Military Medical City (PSMMC) and to identify demographic factors predictive of HCPs’ attitude.MethodsA descriptive–correlational design was used. The study was conducted on a convenience sample of 202 HCPs working in the ED at PSMMC. Data were collected in December of 2022 and analyzed using SPSS v.23. Multiple linear regression analyses were performed separately for the six domains and overall patient safety attitude as dependent variables. For the seven models, the demographic variables were considered predictor variables.ResultsOverall, HCPs demonstrated a positive attitude toward patient safety (Mean = 3.75/5). Among the six domains, job satisfaction scored highest (Mean = 3.96), while stress recognition scored lowest (Mean = 3.54). However, the respondents reported some patient safety issues and agreed on the difficulty in speaking up if they perceived a problem with patient care, as well as in discussing errors. Significant relationships and predictors were established in all six dimensions and in the overall patient safety attitude. The study findings revealed that three demographic variables, namely, certification in ED (p = 0.044), value of patient safety (p = 0.001), and profession (p = 0.014), demonstrated significant correlations with the overall attitude toward patient safety. Furthermore, years of experience as an HCP in ED (p = 0.019), value of patient safety (p = 0.004), and profession (p = 0.047) were identified as predictors of the overall patient safety attitude.ConclusionThe overall attitude of HCPs toward patient safety in the ED at PSMMC was found to be positive across all six domains and overall. Several demographic factors were identified as significantly influencing their positive attitudes toward patient safety. However, some patient safety issues still need to be resolved, needing interventional and strategic solutions from hospital administration. These solutions should take into account, and give high consideration to, the significant demographic factors identified as predictors of HCPs’ attitudes toward patient safety.